The Role of Digital Payment Systems in Enhancing Financial Inclusion in Bilaspur Division: An Empirical Study (International Journal of Food and Nutritional Sciences, 2021)
Within the context of the Bilaspur Division of Chhattisgarh, India, this empirical research investigates the capacity of digital payment systems to contribute to the expansion of financial inclusion. The use of digital payment methods has become vital in bridging the gap between the population that does not have bank accounts and formal financial institutions as a result of the fast digitisation of financial services via the use of digital technology. In order to collect information from a wide range of stakeholders, such as customers, merchants, and suppliers of financial services, the research makes use of a mixed-methods approach, which includes both quantitative surveys and qualitative interviews. According to the findings, digital payment methods greatly enhance accessibility to financial services, especially among populations that are marginalised. A number of important aspects that play a role in the adoption of these systems include the ease of use, the familiarity with digital platforms, and the perception of the safety of financial transactions. The report underlines the good effect that government programs, such as the Digital India campaign, have had in fostering digital literacy and financial awareness among the general population. In addition, obstacles that have been cited as impediments to the achievement of broad financial inclusion include restricted internet access and the digital gap that exists between various socio-economic categories. The findings of this study highlight the need of boosting user education and establishing technological infrastructure that is resilient in order to make the most of the advantages that digital payment systems provide. The findings of this research may provide policymakers and financial institutions with valuable information that can be used to develop policies that promote inclusive economic development and enhance the financial well-being of citizens living in the Bilaspur Division.